Ten years of the program of production engineering at Universidad Centroccidental Lisandro Alvarado (Publicaciones en Ciencias y Tecnología, 2017)
This review presents the achievements of UCLA’s Production Engineering Program after ten years of having started it, in which a total of 205 professionals have graduated, who have trained in different areas of application for the productive sector. The same part of the historical overview of the program, covering the profile and competencies that are achieved in the development of the program, as well as its relationship with the productive sector and the future challenges that are presented.
Keywords: Production engineering; pensum; UCLA; Venezuela